АКТУАЛЬНОСТЬ РЕФОРМИРОВАНИЯ ЮСТИЦИИ - Дука, Тудор, Тарлев Дмитрий (SUPREMANCE OF LAW, 2017)
The author highlights his point of view on the main directions of the reform of the justice of the Republic of Moldova, the state of which leaves much to be desired. The author believes that the reform of justice is impossible without a significant change in the laws governing the procedure for consideration by the courts of civil and criminal cases, as well as laws regulating the enforcement proceedings and activities of lawyers, notaries and bailiffs The author draws attention to certain provisions of the Civil Procedure Code of the Republic of Moldova and the Executive Code of the Republic of Moldova, which impede free access to justice and create favorable conditions for corruption of judges, bailiffs and prosecutors.
Keywords: justice reform; judicial instance; enforcement proceedings; bailiff; judge; prosecutor; lawyer